RESPON SISWA TERHADAP MODEL PEMBELAJARAN RECIPROCAL TEACHING - Sriyanti, Ika (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
ABSTRACTThis research aims to determine students' responses to mathematics learning using the Reciprocal Teaching learning model. The population in this study were all class XI students of Lampang Integrated Vocational School with a sample of class XI OTKP as an experiment. The experimental class was given learning using the Reciprocal Teaching model to determine student responses to mathematics learning and mathematics questions. The instrument used in the research was a non-test in the form of a questionnaire. Questionnaires were distributed after the Reciprocal Teaching lesson was carried out to find out whether students' responses in learning mathematics and filling in mathematics questions increased. The scale used in this research is the Likert scale. Based on the results of the data in this study, it shows that students' responses to mathematics learning using the Reciprocal Teaching model gave a positive response with an average score of 3.1. Students' responses to mathematics learning gave a positive response with an average score of 3.4. Students' responses to mathematics questions gave a positive response with an average score of 3.2. So it can be concluded that the Reciprocal Teaching learning model can be used as an alternative in mathematics learning that can arouse students' enthusiasm and interest.